Synthesis and screening of 6‐alkoxy purine analogs as cell type‐selective apoptotic inducers in Jurkat cells. Issue 10 (15th June 2021) - Lorente‐Macías, Álvaro; Iañez, Inmaculada; Jiménez‐López, M. Carmen; Benítez‐Quesada, Manuel; Torres‐Rusillo, Sara; Díaz‐Mochón, Juan J.; Molina, Ignacio J.; Pineda de las Infantas, María J.
Abstract: Purines are ubiquitous structures in cell biology involved in a multitude of cellular processes, because of which substituted purines and analogs are considered excellent scaffolds in drug design. In this study, we explored the key structural features of a purine‐based proapoptotic hit, 8‐ tert ‐butyl‐9‐phenyl‐6‐benzyloxy‐9 H ‐purine (1 ), by setting up a library of 6‐alkoxy purines with the aim of elucidating the structural requirements that govern its biological activity and to study the cell selectivity of this chemotype. This was done by a phenotypic screening approach based on cell cycle analysis of a panel of six human cancer cell lines, including T cell leukemia Jurkat cells. From this study, two derivatives (12 and 13 ) were identified as Jurkat‐selective proapoptotic compounds, displaying superior potency and cell selectivity than hit 1 . Abstract : A new series of 6‐alkoxy purines was designed, synthesized and evaluated for proapoptotic activity on cancer cells. On the basis of cell cycle analysis, the compound library was screened against a six‐member panel of human cancer cell lines. The cell death induction mechanism and cell viability effects of hit compounds were also examined, showing 12 and 13 as Jurkat cell‐selective (T cell leukemia) proapoptotic compounds.